Health Impact of Chemical Disinfectant Exposures: A Review - Lili Amaliah; Desrialita Faryanti; Abdul Malik Darmin Asri; Supriatin supriatin; Mohamad Sadli; Suyitno Suyitno; Silvia Anitasari (Jurnal Penelitian Pendidikan IPA, 2023)
Chemical disinfectant, such as sodium hypochlorite, bleach and quaternary is crucial for infection prevention. This applies to healthcare settings as well as other settings where the transmission of pathogens can potentially endanger the health of humans and/or animals. Ongoing interdisciplinary research is needed to ensure the effectiveness of disinfectants, understand the process of disinfection, and determine the appropriate timing, methods, and locations for implementing disinfection precautions. To ensure the long-term benefits of disinfection, it is crucial to utilize active substances responsibly and assess their impact on target organisms and the environment through close evaluation and monitoring. Given the worldwide risk posed by communicable diseases, as well as the emergence and resurgence of pathogens that are resistant to multiple drugs, the importance of chemical disinfection is consistently growing. This consensus paper focuses on important factors related to chemical disinfection strategies in healthcare settings, specifically for vulnerable patients